Rwanda : Fourth Review of the Policy Coordination Instrument and Request of an Extension of the Policy Coordination Instrument-Press Release; Staff Report; and Statement by the Executive Director for Rwanda. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2021)
Recent economic developments. Despite a sizeable policy response, the COVID-19 pandemic continues to impact Rwanda's economy and social fabric, with output contracting by 3.4 percent in 2020. The vaccine rollout is expected to help counter the pandemic and support the economic recovery, but risks remain elevated. While progress was made in several reform areas, some envisaged reforms are being delayed. The authorities requested the extension of the program by one year to make progress on ongoing reforms and policies to support the economic recovery and meet their fiscal consolidation and debt objectives. Rwanda received debt relief under the third tranche of the Catastrophe Containment and Relief Trust (CCRT).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Rwanda